2019
DOI: 10.1101/557520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IFNγ induces epigenetic programming of human T-bethiB cells and promotes TLR7/8 and IL-21 induced differentiation

Abstract: 34Although B cells expressing the IFNgR or the IFNg-inducible transcription factor T-bet drive autoimmunity 35 in Systemic Lupus Erythematosus (SLE)-prone mouse models, the role for IFNg signaling in human 36 antibody responses is unknown. We show that elevated levels of IFNg in SLE patients correlate with 37 expansion of the T-bet expressing IgD neg CD27 neg CD11c + CXCR5 neg (DN2) pre-antibody secreting cell 38 (pre-ASC) subset. We demonstrate that naïve B cells form T-bet hi pre-ASCs following stimulation w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 80 publications
3
44
0
Order By: Relevance
“…The fraction of DN B cells lacking CXCR5 and CD21 (DN2 cells) is greatly expanded in patients with active SLE, and this expansion correlates with increased disease activity and poorer outcomes. We also showed that DN2 cells are induced through IFN-γ-IL-21 in a TLR7-dependent fashion 18 , correlate with IL-6 and IP-10 serum concentrations 19 and are epigenetically poised for ASC differentiation through T-bet-driven networks 20 .…”
Section: Extrafollicular B Cell Responses Correlate With Neutralizingmentioning
confidence: 68%
See 1 more Smart Citation
“…The fraction of DN B cells lacking CXCR5 and CD21 (DN2 cells) is greatly expanded in patients with active SLE, and this expansion correlates with increased disease activity and poorer outcomes. We also showed that DN2 cells are induced through IFN-γ-IL-21 in a TLR7-dependent fashion 18 , correlate with IL-6 and IP-10 serum concentrations 19 and are epigenetically poised for ASC differentiation through T-bet-driven networks 20 .…”
Section: Extrafollicular B Cell Responses Correlate With Neutralizingmentioning
confidence: 68%
“…EF response characterization has identified the pathway as peripherally focused, inflammatory, and highly associated with IL-6 and IP-10 (refs. 19,20,32 ). Both of these factors have now been identified as biomarkers of poor prognosis in the COVID-19 literature 1 and could be identified at increased expression in the CoV-A cluster (Fig.…”
Section: Germline Clonotypes Dominate the Covid-19 Asc Repertoirementioning
confidence: 99%
“…). The common factors seem the combination of cytokine signals of IL‐21 and IFN‐γ and the signals via TLR and/or CD40, and cytokine alone is insufficient . The importance of IL‐21 is consistent with high expression of IL‐21 receptor and the IL‐21‐inducible gene signature in SLE CD11c + DN B cells .…”
Section: Introductionmentioning
confidence: 77%
“…Zumaquero et al. showed that the cocktail of TLR7‐ligand, BCR signal, IL‐21, IL‐2, BAFF and IFN‐γ strongly induced naïve B cells to differentiate into CD11c + DN B cells, and IFN‐γ was the most critical among these factors . The differences in the findings are likely caused by differences in the experimental protocols, including in vitro culture system, method to isolate naïve B cells, and the readout phenotype to define CD11c + DN B cells.…”
Section: Introductionmentioning
confidence: 99%
“…17 CD21-low B cells resemble autoreactive CD11c 1 B cells associated with systemic lupus erythematosus, and chronic viral infections have been reported to express the IFN-g inducible transcription factor Tbet and CXCR3. 14,19,38 IFN-g was recently reported to augment the development of autoreactive CD11c 1 B cells, 39 a pathophysiologic link that has also been proposed in CVID. 19 We show correlations of CXCL10 with aberrant T-cell populations in CVID as well as with CD21-low B cells and suggest that the CXCR3 axis is an attractive target for specific treatment to mitigate CVID-related immune dysregulation.…”
Section: Discussionmentioning
confidence: 95%